COOLING LOAD-BASED RETROFITTING OF BRIDGE AIR CONDITIONING SYSTEM TO IMPROVE THERMAL COMFORT AND OPERATIONAL SAFETY ON TB. ANANTA SESA 1 - Windy Jayusman; I Putu Hikariantara; Ulpen Hiermy; Doni Suseno; Mochammad Zoehry (INKOFAR, 2026)
Background The bridge compartment of a vessel serves as the primary operational area where navigation and monitoring activities are conducted continuously. Maintaining an adequate thermal environment with in this space is essential to ensure operator comfort, concentration, and operational safety Purpose This study aimed to evaluate the cooling load requirements of the bridge compartment onboard TB. Ananta Sesa 1 and assess the effectiveness of an air conditioning retrofitting strategy in improving thermal comfort conditions Methodology The research employed a field observation approach combined with cooling load calculations using the Cooling Load Temperature Difference (CLTD) method. Findings Internal heat gains from occupants and navigation equipment, as well as external heat gains from solar radiation, wall and roof heat transfer, and air infiltration, were considered in the analysis. The results indicated that the total cooling load of the bridge compartment reached 15,900 BTU/h, exceeding the capacity of the existing 1 PK air conditioning unit rated at 9,000 BTU/h. To address this deficiency, the existing system was replaced with a 1.5 PK split air conditioning unit utilizing R32 refrigerant. Performance testing demonstrated that the retrofitted system reduced the indoor temperature from 36°C to 25.5°C within 60 minutes of operation. The measured relative humidity remained at approximately 55%, which is consistent with thermal comfort recommendations provided by ASHRAE Standard 55 Implications These findings indicate that the retrofitting strategy successfully improved the cooling performance of the bridge compartment and provided thermal conditions that support operator comfort and safe vessel operation Originality The results may serve as a practical reference for cooling system evaluation and retrofit planning in similar marine applications.